2015
DOI: 10.1051/0004-6361/201525804
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the T Tauri star population in the Lupus association

Abstract: Aims. In a recent study, we derived individual distances for 109 pre-main sequence stars that define the Lupus kinematic association of young stars. Here, we use these new distances to derive the masses and ages of Lupus T Tauri stars with the aim of better constraining the lifetime of their circumstellar disks. Methods. Using the photometric and spectroscopic information available in the literature, we computed the photospheric luminosity of 92 T Tauri stars in the Lupus association. Then, we estimated their … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 55 publications
1
23
1
Order By: Relevance
“…Hughes et al (1994) concluded that Lupus may be a region of sub-critical star formation where magnetic fields slow the collapse of the clouds, leading to low mass accretion rates with the consequence that the lowest mass stars in Lupus are less active than similar objects in other regions. On the other hand, Galli et al (2015) provided evidence that the disc lifetimes may be shorter in Lupus in comparison with those in Taurus. A crucial aspect of the models regarding viscously evolving discs is the presence of the correlations of M disc with M andṀ acc (e.g. Lynden-Bell & Pringle 1974;Hartmann et al 2006;Dullemond et al 2006;Tilling et al 2008, and references therein).…”
Section: Discussionmentioning
confidence: 96%
“…Hughes et al (1994) concluded that Lupus may be a region of sub-critical star formation where magnetic fields slow the collapse of the clouds, leading to low mass accretion rates with the consequence that the lowest mass stars in Lupus are less active than similar objects in other regions. On the other hand, Galli et al (2015) provided evidence that the disc lifetimes may be shorter in Lupus in comparison with those in Taurus. A crucial aspect of the models regarding viscously evolving discs is the presence of the correlations of M disc with M andṀ acc (e.g. Lynden-Bell & Pringle 1974;Hartmann et al 2006;Dullemond et al 2006;Tilling et al 2008, and references therein).…”
Section: Discussionmentioning
confidence: 96%
“…Figure 16. [OI] line profiles and velocity components for "SCJ" objects, ordered by the HVC EWtot,corr to visualize the correlations shown in Figure 6. Stellar masses are taken from Herczeg & Hillenbrand (2014) for Taurus sources and from the compilation in Salyk et al (2013) for sources in other regions, apart from AS353A (Rigliaco et al 2015), DFTau (Allen et al 2017), EXLup (Galli et al 2015), RXJ1615 (Andrews et al 2011), RYLup (Alcalá et al 2017), and V853Oph (Sartori et al 2003). Figure 17. [OI] line profiles and velocity components for objects with no detection or only HVC.…”
Section: Sc-type Lvcmentioning
confidence: 99%
“…Finally, it is also possible that the YSO population of Lupus is different from the populations in other regions. For example, Galli et al (2015) have found that the lifetimes of disks may be shorter in this region than the lifetimes for objects located in the Taurus star-forming region. Although this result relies on individual age estimates, it suggests that objects located in different environments might follow different evolutionary paths.…”
Section: Constraints On Accretion and Disk Evolution Theoriesmentioning
confidence: 99%